2016
DOI: 10.1177/1758834016656493
|View full text |Cite
|
Sign up to set email alerts
|

Safety of long-term exposure to abiraterone acetate in patients with castration-resistant prostate cancer and concomitant cardiovascular risk factors

Abstract: Background: We aimed to evaluate the long-term safety profile of abiraterone in patients with metastatic castration-resistant prostate cancer (mCRPC) with controlled cardiovascular comorbidities or risk factors. Methods: We retrospectively analysed the clinical charts of consecutive mCRPC patients with cardiac disorders/risk factors who had been treated with abiraterone 1000 mg once daily plus prednisone 5 mg twice daily for a median duration of 16 months at an oncology referral centre between April 2011 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…The hematological toxicity related to the treatment with radium-223 is comparable to that registered with the new hormonal treatments, abiraterone and enzalutamide19, 20, 21 and significantly lower than that recorded with cytotoxic chemotherapies (docetaxel and cabazitaxel), in which myelosuppression represents the most frequent toxicity 22, 23. Moreover, radium-223 is distinguished from beta-emitting radiopharmaceuticals, which are associated with significant hematologic events (mainly leukopenia and thrombocytopenia) 24 …”
Section: Discussionmentioning
confidence: 78%
“…The hematological toxicity related to the treatment with radium-223 is comparable to that registered with the new hormonal treatments, abiraterone and enzalutamide19, 20, 21 and significantly lower than that recorded with cytotoxic chemotherapies (docetaxel and cabazitaxel), in which myelosuppression represents the most frequent toxicity 22, 23. Moreover, radium-223 is distinguished from beta-emitting radiopharmaceuticals, which are associated with significant hematologic events (mainly leukopenia and thrombocytopenia) 24 …”
Section: Discussionmentioning
confidence: 78%
“…A population-based retrospective study from The Surveillance, Epidemiology, and End Results (SEER) database of patients using abiraterone or enzalutamide (n = 3,876) revealed that men with coexisting CV comorbidities have a higher mortality threat compared to individuals without a history of CV disorders ( Lu-Yao et al, 2020 ). However, there is also evidence that appropriate control of CV comorbidities before the treatment initiation may substantially reduce the CV risk of the prescribed therapy ( Verzoni et al, 2016 ). Currently, no real-world data studies on CV complications induced by apalutamide or darolutamide are available.…”
Section: Cardiovascular Complications Of Prostate Cancer Treatmentmentioning
confidence: 99%
“… 14 A data update of the same study, with longer follow-up time, confirmed the previously reported safety profile. 15 The results of an additional study, also including mCRPC patients previously treated with DX, were presented at the 2016 American Society of Clinical Oncology Annual Meeting. 16 This was a prospective study specifically aimed at monitoring cardiac functionality during treatment with AA and PDN.…”
Section: Introductionmentioning
confidence: 99%